The future of radiotherapy and immunotherapy concomitantly in cancer management (Medical Journal of Indonesia, 2019)
Immunotherapy is a developing field in cancer treatment. Immunotherapy using immune checkpoint inhibitors has been successful in treating patients with metastatic disease, as well as patients who are refractory to standard treatments. Although immunotherapy has yielded considerably positive outcomes, its clinical benefits are limited to a small subset of patients. A combination of radiotherapy and immunotherapy has been shown to provide greater clinical benefits to more patients. Radiation, particularly hypofractionated radiation with stereotactic radiosurgery or stereotactic body radiotherapy, works by priming T cells, upregulating proinflammatory chemokines, and increasing the immunogenicity of tumor cells. Tumor cells develop immunosuppressive mechanisms that protect them from attack by the immune system. Immunotherapy works by disrupting the ability of tumor cells to setup these defenses. When combined with radiotherapy, it can synergistically enhance tumor cell death via cytotoxic T cells, thus causing systemic tumor regression and generating better clinical response.